Intertekstualitas dalam Puisi Arab: Puisi al-Ḥallāj dan Fārūq Juwaydah - Sammad Hasibuan (Al-Ma‘rifah, 2021)
This study aims to reveal the intertextual found between al-Ḥallāj’s poem (qaṣīdah) and Faruq Juwaidah’s wa Tāba al-Qalb poem. In this case, it refers to the basic assumption of intertext studies, namely that the texts or works that appear today are inseparable from the influence and role of the works that previously existed long before. Furthermore, in intertextual studies, old works that are used as a reference in making new works are called hypograms, while new works written by new authors that appear later are called transformational works. The method in this research is using descriptive analysis method. While the approach used is intertextual. Based on the results of the intertextual analysis conducted by researcher on qaṣīdah al-Ḥallāj and wa-Tāba al-Qalb poem, the researchers found (1) wa-Tāba al-Qalb poem is a form of transformation of qaṣīdah al-Ḥallāj, (2) wa-Tāba al-Qalb poem is the response from qaṣīdah al-Ḥallāj. The results of this study indicate that the impact or influence of old literary works on those that emerged later was very strong.